Biatrial and Biventricular Reference Ranges Based on Cardiac Magnetic Resonance in Sickle Cell Disease Patients Without Heart Damage - Laura Pistoia; Antonella Meloni; Vincenzo Positano; Alessandra Quota; Elisabetta Corigliano; Giuseppe Messina; Stefania Renne; Michela Zerbini; Simona Romani; Gianfranco Sinagra; Lamia Ait Ali; Sophie Mavrogeni; et al. (Diagnostics)
Background/Objectives: We aimed to establish biatrial and biventricular reference ranges using cardiac magnetic resonance (CMR) parameters in SCD patients without heart damage. Methods: This study compared CMR parameters, quantified by cine SSFP sequences, in 48 adult SCD patients without apparent cardiac involvement (defined by the absence of known risk factors, normal electrocardiogram, and no macroscopic myocardial fibrosis or significant cardiac iron on T2* CMR) to matched cohorts of 96 healthy controls and 96 thalassemia major (TM) patients without cardiac damage. Nine paediatric SCD patients were also analysed and compared to age- and gender-matched groups of nine TM patients and nine healthy subjects. Results: In all groups, studied males displayed higher biventricular volumes and mass indexes than females. Male SCD patients showed significantly higher left ventricular (LV) end-diastolic volume index (EDVI), LV end-systolic volume index (ESVI), LV stroke volume index (SVI), cardiac index, LV and right ventricular (RV) mass index, and atrial areas than healthy subjects. Females with SCD exhibited increased LV EDVI, LV SVI, RV mass index, and left atrial area index compared to healthy controls. SCD and TM patients showed comparable biatrial areas and biventricular volumes and function. When compared to TM, SCD males exhibited a larger mass index, while SCD females showed an increased RV mass index. CMR parameters were similar across all paediatric groups. Conclusions: By establishing the biatrial and biventricular reference ranges through CMR for adult male and female SCD patients, we aimed to prevent possible misdiagnosis of cardiomyopathy in this population by taking into account cardiac adaptation due to anaemia.